1990
DOI: 10.1007/bf00563787
|View full text |Cite
|
Sign up to set email alerts
|

Multistage production of Autographa californica nuclear polyhedrosis virus in insect cell cultures

Abstract: The aim of our study was to establish an efficient system for the in vitro production of the insect pathogenic Autographa californica nuclear polyhedrosis virus in a Spodoptera frugiperda cell line. We optimized cultivation conditions for cell proliferation as well as for virus replication in a 1.5 litre stirred tank bioreactor. Cell and virus propagation were found to be optimal at a constant oxygen tension of 40%. In order to provide sufficient nutrients during virus synthesis filtration and perfusion device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Glucose uptake was similar in the two cases, but lactate accumulated significantly in the bioreactor indicating inadequate oxygen supply. Kloppinger et al (1990) found that a dissolved oxygen concentration of 40% was necessary to optimize the production of wild-type virus in a bioreactor. In a bioreactor infection with Sf-9 cells at 6 × 10 5 cells/mL, found that the dissolved oxygen fell to zero and stayed there for 90 h without DO control.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose uptake was similar in the two cases, but lactate accumulated significantly in the bioreactor indicating inadequate oxygen supply. Kloppinger et al (1990) found that a dissolved oxygen concentration of 40% was necessary to optimize the production of wild-type virus in a bioreactor. In a bioreactor infection with Sf-9 cells at 6 × 10 5 cells/mL, found that the dissolved oxygen fell to zero and stayed there for 90 h without DO control.…”
Section: Discussionmentioning
confidence: 99%
“…More resent work indicates that the cultivation of mammalian cells generally can be undertaken satisfactorily from 5% to 100% of air saturation (Oh et al 1989). Insect cells have been reported to have a narrower operating range of 40-60% (Klopinger et al 1990), though there is also some work indicating that they are similar to mammalian cells (Kioukia et al 1996). The overall oxygen demand of the cells throughout the cultivation (including post-infection in the case of insect cells) must be met by the oxygen transfer rate and the demand increases as long as the number of viable cells is increasing.…”
Section: Mass Transfer Performance and Oxygen Demandmentioning
confidence: 99%
“…Optimum dO 2 levels for cultivation (Klopinger et al 1990) from 40% to 60% potentially give a reduced driving force for oxygen transfer. Both these aspects suggest that insect cells may require higher agitation and/or aeration intensity.…”
Section: Insect Culture Post-infectionmentioning
confidence: 99%
“…The optimal pO 2 value for Sf-9 cell growth is, however, dependent upon the medium and bioreactor type used. In fact, in serum-containing medium, in a 1.5 dm 3 stirred tank with bubble-free aeration the specific growth rate at a pO 2 of 60 or 80% was lower than the one measured at 20 and 40% (Klöppinger et al, 1990). In 18 dm 3 stirred tanks with microsparging, pO 2 values of 10 and 110% lead to a reduction of 25% in the specific growth rate when compared to a pO 2 of 65% (Jain et al, 1991).…”
Section: Discussionmentioning
confidence: 64%